Pengaruh Ketaatan Aturan Akuntansi, Efektivitas Sistem Pengendalian Internal, Kesesuaian Kompensasi, dan Asimetri Informasi Terhadap Kecenderungan Kecurangan Akuntansi - Denov Irnadianis Ifada; Dewi Indriasih; Aminul Fajri (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2026)
This research aims to determine the impact of accounting compliance, internal control system effectiveness, compensation suitability, and information asymmetry on the likelihood of fraud in village offices in Brebes Regency. The target group of this research is village offices in Brebes Regency consisting of four villages. The sampling technique is purposive sampling consisting of village heads, village secretaries, village treasurers, heads of government sections, and government staff with a total of 34 respondents. Data collection was carried out by distributing questionnaires to respondents. This study utilizes primary data as the main source. The approach used is a descriptive quantitative method. To analyze the data, multiple linear regression techniques were used with the help of IBM SPSS version 22 software. This study provides evidence that accounting compliance has a significant negative effect on the potential for accounting fraud. Meanwhile, the effectiveness of the internal control system shows an insignificant negative effect on the likelihood of accounting fraud. On the other hand, the suitability of compensation is proven to have a significant negative impact on the likelihood of accounting fraud. Meanwhile, information asymmetry has a positive effect on the likelihood of accounting fraud. Keywords: Accounting Rule Compliance, Internal Control System Effectiveness, Compensation Suitability, Information Asymmetry, Accounting Fraud Proneness.